Pengaruh Efikasi Diri dan Persepsi Profesi Guru terhadap Minat Mahasiswa Pendidikan Ekonomi Universitas Siliwangi - Wanda Azizah; Yoni Hermawan; Gugum Gumilar (LPPM UM Metro, 2026)
This study is driven by a critical issue role of student interest in determining professional careers as economic educators amidst challenges in the quality of study decision-making. The study aims to determine the influence of self-efficacy and perception of the teaching profession on the interest in becoming an economic teacher among Economic Education students at Siliwangi University, cohorts 2022 and 2023. The research methodology employed is quantitative descriptive with an explanatory design. The population consisted of 261 students, with a sample of 158 respondents selected via proportional random sampling. Data were collected through questionnaires and analyzed using multiple linear regression via SPSS 26. The results indicate that self-efficacy and perception of the teaching profession, both partially and simultaneously, have a positive and significant influence on the interest in becoming an economic teacher. The coefficient of determination R2 of 65.5% demonstrates a strong contribution from both variables. In conclusion, strengthening belief in one’s own abilities coupled with a positive view of the teacher's professional image are key factors in increasing student professional interest. These findings recommend the necessity of enhancing field practices and integrative career motivation programs within higher education environments.